RUSSIAN UNIVERSITIES IN GLOBAL RATINGS - Ildar U. Zul'karnay; Guzel R. Islakaeva (Moscow Polytechnic University, 2016)
This paper conducts comparative analysis of Russian universities' positions in international and Russian rating systems. Particular attention is paid to universities that have obtained special statuses: "Federal University", "National Research University" and also to universities that participate in federal project "5-100". This project targets the Russian